Training the Next Generation of Pathologists: A Novel Residency Program Curriculum at Montefiore Medical Center/Albert Einstein College of Medicine. (27th May 2019) - Hébert, Tiffany Michele; Cole, Adam; Panarelli, Nicole; Hu, Shaomin; Jacob, Jack; Ahlstedt, Jeffrey; Steinberg, Jacob J.; Prystowsky, Michael B
Pathology residency training is currently a time-intensive process, frequently extending up to 6 years in duration as residents complete 1 or 2 fellowships following graduation. Innovative training curricula may help address the impending changes in the health-care landscape, particularly future shortfalls in pathology staffing and changing health-care models that incorporate more work within interdisciplinary teams. Montefiore has created a novel residency training program aimed at accelerating the acquisition of competency in pathology, preparing residents for independent practice at the completion of residency training, and providing residents with the requisite adaptability and consultative skills to excel wherever they choose to practice. We describe the implementation of this novel pathology residency training curriculum at Montefiore Medical Center/Albert Einstein College of Medicine and the perception of residents in both the old curriculum and the new curriculum.